2009
DOI: 10.4067/s0718-48832009000200004
|View full text |Cite
|
Sign up to set email alerts
|

Word-Frequency and Vocabulary Acquisition: An Analysis of Elementary Spanish College Textbooks in the Usa

Abstract: At universities in the United States, first-year Spanish instructors often wonder why their students perform below expectations in vocabulary tests. This paper addresses this question by presenting an analysis of five leading first-year college Spanish textbooks published in the United States. This analysis consists of two parts: 1) mapping the textbooks' vocabulary lists as well as the vocabulary that appears in their reading input against the vocabulary-frequency information provided in A frequency dictionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Over the length of a text, certain terms may be repeated. The frequency of their recurrence has been referred to as the “vocabulary frequency,” which quantifies the number of times a learner comes into contact with specific terms ( Godev, 2009 ). It is suggested that increasing the number of times a learner encounters a term will deepen his or her learning of that term ( Urzúa et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the length of a text, certain terms may be repeated. The frequency of their recurrence has been referred to as the “vocabulary frequency,” which quantifies the number of times a learner comes into contact with specific terms ( Godev, 2009 ). It is suggested that increasing the number of times a learner encounters a term will deepen his or her learning of that term ( Urzúa et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that increasing the number of times a learner encounters a term will deepen his or her learning of that term ( Urzúa et al. , 2006 , in Godev, 2009 ). According to Tzeng et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with ignorance of those words that are strewn all over the text, which potentially compromises the comprehension of the several parts of the text in which they are used. High frequency of a word in a text guarantees learner contact with it (Godev 2009) and impacts their textual comprehension.…”
Section: The Efficacy Of High Frequency Wordsmentioning
confidence: 99%
“…The role of words in communication has been deemed analogous to that of molecules in physical structures (Eskey & Grabe 1988), where the former constitutes the existence of the latter. Vocabulary knowledge is considered predictive and reflective of reading achievement (Pikulski & Templeton 2004;Godev 2009). …”
Section: Importance Of Vocabulary Knowledgementioning
confidence: 99%